KREATIVITAS GURU DALAM PENGEMBANGAN SUMBER DAN METODE AJAR UNTUK PENCAPAIAN TUJUAN PENDIDIKAN AGAMA KRISTEN - Heryanto Heryanto (Lembaga Penenlitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Darma Agung, 2019)
The education always requires teaching, but not all teaching is education. Educational cases are conceit of teachers who always have an important role n educational process. One assumption said that the teacher influences teaching and learning process. Therefore, the teacher should have a good ability and skill to teach. For this reason, it takes a professional teacher who is creative in teaching.